2021
DOI: 10.7759/cureus.15459
|View full text |Cite
|
Sign up to set email alerts
|

A Rare and Unusual Case of Trisomy 10p with Terminal 14q Deletion: A Multidisciplinary Approach

Abstract: Trisomy 10p is a rare entity to be diagnosed and so is terminal 14q deletion. The total number of trisomy 10p cases reported to date is estimated to be in double digits. The number of terminal 14q deletion cases that have been reported in the literature is even lesser than that of trisomy 10p. Simultaneous occurrence of these genetic aberrations is, therefore, extremely rare. Herein, we document a case of a 14-month-old female diagnosed with trisomy 10p and terminal 14q deletion, who presented with an inabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Despite variation observed over the phenotypic spectrum, trisomy 10p demonstrates discernible multiple congenital anomalies/mental retardation (MCA/MR) syndrome [11,27,28]. In conformation to the case report on GNS, absence of cardiopulmonary malformations has been observed in other previous studies on trisomy 10p [1,[13][14][15]. One of the studies reported features resembling facio-auriculo-vertebral spectrum in a child with trisomy 10p [29].…”
Section: Phenotypementioning
confidence: 93%
See 4 more Smart Citations
“…Despite variation observed over the phenotypic spectrum, trisomy 10p demonstrates discernible multiple congenital anomalies/mental retardation (MCA/MR) syndrome [11,27,28]. In conformation to the case report on GNS, absence of cardiopulmonary malformations has been observed in other previous studies on trisomy 10p [1,[13][14][15]. One of the studies reported features resembling facio-auriculo-vertebral spectrum in a child with trisomy 10p [29].…”
Section: Phenotypementioning
confidence: 93%
“…Some striking features in the hand that can aid clinical diagnosis are atypical palmar creases like formation of a triangle, camptodactyly and clinodactyly [7,11,14,[18][19][20]24]. The first case report on GNS also reported similar findings in context of hand [1]. It is interesting to note that around 20% of males presenting with duplication of 10p displayed intersex condition [7].…”
Section: Phenotypementioning
confidence: 94%
See 3 more Smart Citations